The fetal position : a rational approach to the abortion debate - Meyers, Chris, 1968- (Amherst, N.Y. : Prometheus Books, 2010)
Provides a philosophical analysis of some of the most common arguments on both sides of the abortion issue as an example of engaging critical thinking for moral issues.
Philosophy to the rescue -- What is the soul? -- Life begins at conception. So what? -- Abnormal human development -- Responsibility -- The potentiality argument -- The golden rule argument against abortion -- Rights of the pregnant woman -- Consequences -- Virtue.
Includes bibliographical references and index.
Keywords: Abortion -- Moral and ethical aspects